Desakralisasi Talak dalam Masyarakat Muslim Indonesia: Analisis Maqashid al-Sharī‘ah terhadap Praktik Talak Bercanda - Windi Anastasya Siregar; Ahmad Zuhri Rangkuti (Universitas Islam Negeri Sumatera Utara, 2026)
Abstract: This study examines the phenomenon of the desacralization of ṭalāq in Indonesian Muslim society through a maqāṣid al-sharī‘ah perspective, focusing on the practice of joking divorce in Puji Mulyo Village, Sunggal District, Deli Serdang Regency, North Sumatra. In Islamic law, ṭalāq constitutes a sacred legal instrument and serves as an ultimum remedium in resolving marital conflicts. However, contemporary social practices demonstrate that ṭalāq is frequently used as a joke, emotional threat, or ordinary expression in domestic interactions, resulting in a gradual shift from a sacred legal act to a profane verbal expression. This research employs an empirical legal research method with a qualitative approach and thematic analysis. Data were collected through interviews, observation, and documentation involving ten household cases in which ṭalāq was used beyond its normative legal function. The findings reveal six stages of ṭalāq desacralization: ṭalāq as a joke, ṭalāq as an instrument of emotional pressure, repeated ṭalāq without legal awareness, ṭalāq as a relational language, the banality of ṭalāq in marital conflicts, and total desacralization. These stages indicate a gradual transformation of ṭalāq from a sacred legal institution into an ordinary verbal practice detached from its normative and ethical foundations. From the perspective of maqāṣid al-sharī‘ah, such practices undermine the protection of lineage (ḥifẓ al-nasl), human dignity (ḥifẓ al-‘irḍ), and legal and intellectual awareness (ḥifẓ al-‘aql). This study contributes to Islamic family law scholarship by proposing a conceptual model of the stages of ṭalāq desacralization and emphasizing the need to reconstruct the sacred understanding of divorce through legal literacy, family education, and a maqāṣid-oriented approach to family law. Keywords: Ṭalāq Desacralization; Joking Divorce; Islamic Family Law; Maqāṣid al-Sharī‘ah; Legal Culture.